The virtue of obedience - Shaw, J (Cambridge University Press, 2002)
In this paper I give an account and defence of the thought and practice associated with the notion of obedience in religious ethics, especially in reply to the claim that obedience is necessarily unconscientious. First, I argue that it is conscientious to give weight to commands if they are identifiable as pieces of authoritative advice, or, as theists commonly believe, if they have intrinsic moral force. Second, I argue that a theist's strictly moral reasons for fulfilling obligations are not replaced but reinforced by reasons arising out of a personal relationship with God. Anyone who loves God will want to please God, to act in accordance with His teaching and to avoid His punishment, and theists can do these things by respecting existing moral reasons for action. Third, I show how it can be valuable that people submit to God in further ways, by doing what God commends, and by committing themselves to obeying divine commands which would not otherwise be addressed to them. Finally, I argue that subordinating oneself to God's will is itself a partial attainment of the spiritual ideal of mystical union with God.